Expression of CCL22 and Infiltration by Regulatory T Cells are Increased in the Decidua of Human Miscarriage Placentas. (28th April 2015) - Freier, Christoph P.; Kuhn, Christina; Rapp, Moritz; Endres, Stefan; Mayr, Doris; Friese, Klaus; Anz, David; Jeschke, Udo
<x xml:space="preserve">Abstract</x> Problem Regulatory T cells (Treg) are a T‐cell subpopulation with suppressive capacities, specifically attracted by CCL22. We aimed to investigate whether CCL22 is expressed in human placentas and whether its presence, together with Treg infiltration, is associated with miscarriage conditions. Method of study Paraffin samples were stained for CCL22 and for the Treg‐specific transcription factor FoxP3. Expression levels were evaluated in a semi‐quantitative manner. Double immunofluorescence was used for the identification of CCL22‐producing cells. Results In all placentas, trophoblasts expressed CCL22. Interestingly, expression in the decidua was only observed in miscarriage conditions. Maternal stromal cells expressed CCL22. Correlation with a higher presence of Treg in the decidua of abortive tissues was observed. Conclusion Our results demonstrate that CCL22 is expressed in human placenta. Decidual expression was only observed in miscarriage conditions and correlates with Treg infiltration. Thus, CCL22 plays a role in human pregnancy and may occur as a negative feedback response to pro‐inflammatory events during miscarriage conditions.